Praktik Kuasa Platform Media Sosial Di Balik Kecanduan Media Sosial Bagi Remaja - Koli, Nicodemus (Bina Nusantara University, 2024)
In the present time, browsing through social media via smartphones is one of the top reasons for using the internet. Through social media, everyone has a space to express their thoughts, feelings, actions, and attitudes easily and quickly. The personality traits, interests, and preferences of every individual are readable, peeked into, and monitored. Every symbol, advertisement, information, and product promotion that aligns with the user's desires and character is continuously presented by social media platforms. Experts who have careers and strategic positions, as well as being the creators of various captivating control features in companies like Google and Facebook, along with scientists, discuss this issue clearly in a series of interviews that are later presented in the documentary film